Pengaruh Free Cash Flow, Kepemilikan Manajerial, dan Kepemilikan Institusional Terhadap Kebijakan Dividen - Diva Aura Putri Wiyanto; Luh Gede Sri Artini (Universitas Veteran Bangun Nusantara, 2024)
Dividends are one of the reasons investors make investments, but there are very few property and real estate companies that distribute dividends regularly. This study aims to test and explain the effect of free cash flow, managerial ownership, and institutional ownership on dividend policy. Secondary data in this study were obtained from the official website of the Indonesia Stock Exchange. The population in this study were property and real estate companies for the 2019-2023 period with a sample of 7 companies taken using the purposive sampling method. The analysis technique used was multiple linear regression analysis. The findings of this study are that free cash flow partially has no effect on dividend policy. A high percentage of managerial ownership has a positive impact on the amount of dividends distributed. High institutional ownership can minimize agency costs and increase the amount of dividends distributed.